2021
DOI: 10.3389/fmars.2021.703818
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Spinner Dolphin (Stenella longirostris) Occurrence and Acoustic Activity in the Maui Nui Region

Abstract: Hawaiian spinner dolphins (Stenella longirostris) rest during the day in the islands’ coastal waters where they are susceptible to human disturbance. Due to concerns over the negative impacts of human activity, the Pacific Islands Regional Office of the National Oceanic and Atmospheric Administration (NOAA) has proposed a 50-yard approach rule for spinner dolphins and is also considering time-area closures of certain important spinner dolphin resting areas. However, gaps still persist in the understanding of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Snapping shrimp activity contributed most to the ambient noise in our dataset and showed distinct day− night differences. Dolphin detections also showed distinct day−night patterns in our study, and such patterns have been reported in other studies as well (Lammers et al 2008, McElligott 2018, Cascão et al 2020, McElligott & Lammers 2021. Because ambient noise had a strong diel pattern, it is difficult to know if the diel pattern in dolphin detections we observed was caused by true diel differences in behaviour (e.g.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Snapping shrimp activity contributed most to the ambient noise in our dataset and showed distinct day− night differences. Dolphin detections also showed distinct day−night patterns in our study, and such patterns have been reported in other studies as well (Lammers et al 2008, McElligott 2018, Cascão et al 2020, McElligott & Lammers 2021. Because ambient noise had a strong diel pattern, it is difficult to know if the diel pattern in dolphin detections we observed was caused by true diel differences in behaviour (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, we suspect that populations in our study area may be similar to populations off other isolated single-island habitats where site fidelity is high, and resident dolphin populations may be fairly isolated and therefore more vulnerable to anthropogenic disturbances (Karczmarski et al 2005). Information on the abundance, distribution, and community composition of cetaceans, such as that presented in our study, prior to large-scale tourism is critical to designing adequate regulations in this area and may act as a useful baseline with which to monitor any future trends (McElligott & Lammers 2021). We recommend further finescale visual and acoustic studies that can inform policy makers and establish no-go zones, times or seasons in upcoming tourism plans and environment impact assessments.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Passive acoustic monitoring has become popular for studying dolphin diel patterns, which seem to vary across and within taxa. Several studies have found that dolphins are most vocally active at night (Deconto et al, 2016;Dede et al, 2014;Frouin-Mouy, 2022;Hodge et al, 2013), while others found that dolphins are most vocally active during the day (Gauger et al, 2022;McElligott & Lammers, 2021) or during twilight hours (Goold, 2000), or showed no observable diel pattern in vocalization rates (Philpott et al, 2007). One study found different diel patterns for different types of vocalizations (Cascão et al, 2020), while another found a nocturnal diel pattern in the vocalizations of smaller dolphin species while larger species were vocally active throughout the diel cycle (Howe & Lammers, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Massachusetts Bay and Stellwagen Bank the opposite was seen with likely Atlantic white-sided and/or common dolphins, with the fewest amount of whistles occurring around midday and peaks in whistle activity during the night (Silva et al, 2019b). Hawaiian spinner dolphins emit more whistles during the morning before their resting period then utilize echolocation clicks during the night for foraging on the deep scattering layer (Heenehan et al, 2016;McElligott and Lammers, 2021). The diversity in vocalization behavior and site usage observed in NMS highlights the potential importance of these areas for different aspects of the life history of numerous delphinid species.…”
Section: Introductionmentioning
confidence: 99%